Preparation of citrus planting material: Socialization in the ecotourism activist community at Pajagan Village, Cisitu Sub-District, Sumedang Regency - Budiarto, Rahmat; Mubarok, Syariful; Kusumiyati, Kusumiyati; Farida, Farida; Sutari, Wawan; Soleh, Mochamad Arief; Djaya, Luciana; Rasiska, Siska (Research and Social Study Institute, 2024)
The present community service was aimed to socialize techniques for preparing citrus planting materials in the ecotourism activist community at Pajagan Village, Cisitu District, Sumedang Regency. The socialization was attended by 30 people who were a combination of academics, representatives of Pajagan village-owned enterprise (Bumdes), and ecotourism activists whose daily professions are farmers in the Cipicung farmer group, Pajagan. To produce citrus planting material, grafting is a prerequisite vegetative propagation technique for obtaining standardized tangerine planting material. Grafted seedlings are more recommended than seed originated seedling, because of flower quickly, resistant to damping off, pests and diseases. Grafting is performed to connect the upper stem/scion of a tangerine cv. Siam Madu with superior fruit characteristics and the lower stem/rootstock of a sour rough lemon (Citrus jambhiri). It is hoped that this outreach activity can grow public interest and knowledge in producing planting material independently in the future.